2012
DOI: 10.1002/mds.25214
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of surgical therapies for Parkinson's disease

Abstract: The surgical lesion of different brain structures has been used as a treatment for Parkinson's disease (PD) for several decades. More recently, the favored therapeutic approach has involved the administration of levodopa and the use of DBS. These two major therapeutic advances have greatly modified both the clinical condition of patients and the history of the disease. With the introduction of L‐dopa in 1967, patients could regain mobility, because their akinesia, tremor, and rigidity were greatly improved, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 68 publications
(193 reference statements)
5
86
0
10
Order By: Relevance
“…The clinical improvement found in this study is in line with previous publications (3,7,10,12). In our study population we observed one case of transient hemiballismus and one case of transient hypomania after STN DBS.…”
Section: Discussionsupporting
confidence: 93%
“…The clinical improvement found in this study is in line with previous publications (3,7,10,12). In our study population we observed one case of transient hemiballismus and one case of transient hypomania after STN DBS.…”
Section: Discussionsupporting
confidence: 93%
“…117 Surgical treatment of Parkinson's disease has given rise to a new phenotype of patients with advanced Parkinson's disease who have little akinesia, no tremor or rigidity, and little dyskinesia, and are mainly disabled by frontal dementia, apathy, and levodoparesistant axial motor features. 118 Diff erent mechanisms might therefore underlie early and potentially reversible postoperative apathy and more tardive non-reversible apathy. Whereas the early and potentially reversible form of apathy occurs in the context of withdrawal of dopaminergic drugs, the tardive non-reversible form seems more related to cognitive deterioration and progression of synucleino pathy, which is transmitted by projection neurons to their target Review neurons.…”
Section: Apathy After Deep Brain Stimulation In Parkinson's Diseasementioning
confidence: 99%
“…The benefits of subthalamotomy have been reported to persist for a follow-up of 3e6 years [2]. Some loss of benefit over time however has been noted in a subpopulation [2] whereas the benefit was maintained up to 24 months in some patients [4] while long-term STN stimulation efficacy with stable effect on tremor and rigidity has been reported with a follow-up of 5e10 years [1]. STN stimulation is a reversible and adaptable treatment and the stimulation of each STN can be separately adjusted over time, which is not possible with subthalamotomy.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…STN stimulation is a reversible and adaptable treatment and the stimulation of each STN can be separately adjusted over time, which is not possible with subthalamotomy. However, despite long-term efficacy of surgical therapies for PD, there is a progressive worsening of the disease inevitably leading to disability in the very long term related to disease progression (worsening of akinesia, postural instability, dysarthria and swallowing difficulties, cognitive deterioration) following both STN stimulation and STN lesion [1].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation